Fed-Batch mcl- Polyhydroxyalkanoates Production in Pseudomonas putida KT2440 and ΔphaZ Mutant on Biodiesel-Derived Crude Glycerol - Borrero-de Acuña, José Manuel; Rohde, Manfred; Saldias, Cesar; Poblete-Castro, Ignacio (Frontiers in Bioengineering and Biotechnology, 2021)
Crude glycerol has emerged as a suitable feedstock for the biotechnological production of various industrial chemicals given its high surplus catalyzed by the biodiesel industry. Pseudomonas bacteria metabolize the polyol into several biopolymers, including alginate and medium-chain-length poly(3-hydroxyalkanoates) (mcl-PHAs). Although P. putida is a suited platform to derive these polyoxoesters from crude glycerol, the attained concentrations in batch and fed-batch cultures are still low. In this study, we employed P. putida KT2440 and the hyper-PHA producer ΔphaZ mutant in two different fed-batch modes to synthesize mcl-PHAs from raw glycerol. Initially, the cells grew in a batch phase (μmax 0.21 h–1) for 22 h followed by a carbon-limiting exponential feeding, where the specific growth rate was set at 0.1 (h–1), resulting in a cell dry weight (CDW) of nearly 50 (g L–1) at 40 h cultivation. During the PHA production stage, we supplied the substrate at a constant rate of 50 (g h–1), where the KT2440 and the ΔphaZ produced 9.7 and 12.7 gPHA L–1, respectively, after 60 h cultivation. We next evaluated the PHA production ability of the P. putida strains using a DO-stat approach under nitrogen depletion. Citric acid was the main by-product secreted by the cells, accumulating in the culture broth up to 48 (g L–1) under nitrogen limitation. The mutant ΔphaZ amassed 38.9% of the CDW as mcl-PHA and exhibited a specific PHA volumetric productivity of 0.34 (g L–1 h–1), 48% higher than the parental KT2440 under the same growth conditions. The biosynthesized mcl-PHAs had average molecular weights ranging from 460 to 505 KDa and a polydispersity index (PDI) of 2.4–2.6. Here, we demonstrated that the DO-stat feeding approach in high cell density cultures enables the high yield production of mcl-PHA in P. putida strains using the industrial crude glycerol, where the fed-batch process selection is essential to exploit the superior biopolymer production hallmarks of engineered bacterial strains.